2011
DOI: 10.15835/nbha3915853
|View full text |Cite
|
Sign up to set email alerts
|

Forage Yield and the Quality of Perennial Legume-Grass Mixtures under Rainfed Conditions

Abstract: This study was performed to determine suitable perennial forage species and their mixtures for the establishment of short-term artificial pastures under rainfed conditions in Turkey. The study was conducted from 2008 through 2010. Alfalfa (Medicago sativa L.), sainfoin (Onobrychis sativa Lam.), brome grass (Bromus inermis Leys.), intermediate wheatgrass (Agropyron intermedium (Host). Beauv.), crested wheatgrass (Agropyron cristatum L. Gaertn.) and their binary and ternary mixtures were used as experimental mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 21 publications
4
44
1
Order By: Relevance
“…This was probably due to the relative stability of the cellulose content of grasses and legumes (Weiss et al, 2002 results showed that the ADF content of C. pubescens was significantly (P<0.05) higher than C. ternatea and S. splendida. In relation to the digestibility C. pubescens have lower digestibility than C. ternatea and S. splendida (Albayrak et al, 2011). The results also illustrated that the ADF content of legumes was not always lower than the grass.…”
Section: Neutral Detergent Fibre (Ndf) Based Onmentioning
confidence: 76%
See 2 more Smart Citations
“…This was probably due to the relative stability of the cellulose content of grasses and legumes (Weiss et al, 2002 results showed that the ADF content of C. pubescens was significantly (P<0.05) higher than C. ternatea and S. splendida. In relation to the digestibility C. pubescens have lower digestibility than C. ternatea and S. splendida (Albayrak et al, 2011). The results also illustrated that the ADF content of legumes was not always lower than the grass.…”
Section: Neutral Detergent Fibre (Ndf) Based Onmentioning
confidence: 76%
“…Proportion of S. splendida ( ) and C. pubescens (□) in mix cropping plot at each harvest Figure 1b. Proportion of S. splendida ( ) and C. ternatea (□) in mixed cropping plot at each harvest Buyukburc, 2004;Albayrak et al, 2011;Eskandari, 2012;Njad et al, 2013) who reported that grass intercropped with legume resulted in improved soil fertility through the addition nitrogen by fixation and excretion from the legume component and also increased CP content of nearby grass. The CP content of S. splendida that were planted in peatland was slightly lower than the average CP content of S. splendida reported by Heuzé & Tran (2012) who showed that the CP content of S. splendida was 9.1%.…”
Section: Stylosanthes Guianensis)mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding demonstrated that mixtures were advantageous compared to their pure stands. Some researchers emphasized on the advantages of intercropping (Albayrak and Ekiz, 2005, Albayrak et al, 2011, Atis et al, 2012. LER value was significantly influenced by the years and mixtures.…”
Section: Land Equivalent Ratio (Ler)mentioning
confidence: 99%
“…Their productivity is higher, as each species in the mixture contributes in various degree for the increase of the dry matter yield [ELESSESSER, 2004;FRAME, 2005;VASILEV et al, 2005;ALBAYRAK et al, 2011;VASILEVA, 2011VASILEVA, , 2014STEVANOVIC et al, 2015] and demonstrates a higher quality and better seasonal distribution of the forage yield [SLEUGH et al, 2000;ANNICCHIARICO, 2008] . The development of the plants in the combined crops creates various relationships among them.…”
Section: Introductionmentioning
confidence: 99%